Electronic structure and optical properties of Cu3PX4(X=S and Se): Solar cell made of abundant materials. (November 2015) - Slassi, Amine
Abstract: The electronic structure and optical properties of Cu3 PX4 (X=S and Se) have been investigated employing the full potential linearized augmented plane wave (FP-LAPW) method. The modified Becke–Johnson exchange potential (TB-mBJ) was used along with the generalized gradient approximation proposed by of Perdew–Burke–Ernzerhof (GGA-PBE) to treat the exchange-correlation contribution. Our results are found to be exceptionally in good agreement with exciting theoretical and experimental data. The calculated band structure shows a direct band gap of 1.376 eV for Cu3 PSe4 and an indirect band gap of 1.87 eV for Cu3 PSe4 . The band gap dependent on optical properties such as dielectric function and absorption coefficient are predicted within this study. The optical responses suggest that Cu3 PSe4 is promising as a photovoltaic material thanks to its high absorption coefficient and photoconductivity in the visible light.